Infiltration by Streptococcus mutans in provisional crowns fixed by two types of cementing agents – pilot double-blind randomized clinical trial - Rego, Ana Luiza Aquino; Moura, Vanessa Anielly Cruz; Prado, Janaína Câncio de Holanda; Alexandrino, Francisca Jamila Ricarte; Regis, Romulo Rocha; Pontes, Karina Matthes de Freitas (Journal of Health & Biological Sciences, 2021)
Objective: When provisional acrylic crowns are used for a long time, they become more susceptible to marginal leakage by cariogenic bacteria. The objectives of this pilot clinical study were to compare cement based on zinc oxide-eugenol and calcium hydroxide by contamination with Streptococcus mutans, and calculate the sample size for the continuation of this study. Methods: Individuals receiving provisional crowns and following inclusion/exclusion criteria, were randomly distributed into 2 groups: zinc oxide-eugenol (n=8); calcium hydroxide (n=9). The temporary crowns were made by a blind researcher and cemented by another. Patients were also blinded by the cement used inside their crowns. After 2 months, a cement sample from the crowns’ peripheral inner face was collected, placed in a tube containing 1 mL of sterile saline, serially diluted, plated on Mitis Salivarius Bacitracin agar, and incubated for 48 hours. Colony-forming units (CFU/mL) were counted. A statistical power analysis was performed to calculate sample size (1-β=80%) and the Mann Whitney test to compare both cements (α=0.05). Results: Both cements were contaminated with S. mutans, with an average of 166.6 x 102 CFU/mL for calcium hydroxide and 435.3 x 102 CFU/mL for zinc oxide-eugenol, with no significant difference (p=0.311). The sample size calculated for this study was 36 per group. Conclusion: This pilot study suggests that there is important contamination inside provisional crowns used for two months, independent of the cement. The continuation of this study is needed, with a bigger sample size, to enable a comparison between the cements.